2004
DOI: 10.1373/clinchem.2004.036111
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Assay Based on Gliadin-Related Nonapeptides as a Highly Sensitive and Specific Diagnostic Aid in Celiac Disease

Abstract: Background: Celiac disease (CD) is induced by wheat gliadins and related cereal proteins. Anti-gliadin antibodies (AGAs) are present in the serum of CD patients, but these antibodies have lower diagnostic specificity and sensitivity than autoantibodies [anti-endomysium antibodies (AEmAs) and anti-tissue transglutaminase antibodies (AtTGAs)]. Recently, AGAs from CD patients were found to recognize deamidated gliadin peptides, probably formed by the action of tissue transglutaminase. Methods: We synthesized seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(113 citation statements)
references
References 35 publications
4
105
1
2
Order By: Relevance
“…To sum up, our study confirms the preliminary data published by other authors, in which it is evident that AGA tests using deamidated gliadin peptides give excellent results in the diagnosis of CD patients (18,19,32). Our very heterogeneous case study demonstrates the particular diagnostic efficiency of the AGAs class IgG tests.…”
Section: Discussionsupporting
confidence: 89%
“…To sum up, our study confirms the preliminary data published by other authors, in which it is evident that AGA tests using deamidated gliadin peptides give excellent results in the diagnosis of CD patients (18,19,32). Our very heterogeneous case study demonstrates the particular diagnostic efficiency of the AGAs class IgG tests.…”
Section: Discussionsupporting
confidence: 89%
“…In recent years it has been shown that the new anti-DGP ELISA tests using deamidated gliadin peptides as antigen have a high sensitivity and a specificity comparable to those of anti-tTG and EMA and higher than AGA (25,(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Schwertz et al (38) demonstrated that an immunoassay based on deamidated synthetic gliadin peptides (DGP) bound to nitrocellulose filters were recognized by sera of CD patients. The recognition of the epitopes containing the sequence QPEQPFP showed high specificity for CD.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence support retrotransport of SIgA-gliadin complexes in active CD. First, the intestinal lumen of patients with active CD contains elevated levels of antigliadin IgA antibodies ( 17 ), which can bind a set of gliadin peptides ( 42,43 ) including the 33-mer ( 44 ) and p31-55 ( 45 ). We show the presence of high molecular weight gliadin-specifi c IgA immune complexes containing Tgase.…”
Section: Iga Mediates the Intestinal Transport Of Intact 33-mer Via Cd71mentioning
confidence: 99%